Enough about the baby : a brutally honest guide to surviving the first year of motherhood - Vieira, Becky (Union Square & Co., 2023)
"Enough already with all those guides solely focused on caring for a screaming, crying, pooping infant! New moms deserve better. Writer Becky Vieira wants to help them unapologetically prioritize self-care, create healthy boundaries, and stay sane in our newborn-obsessed culture. Drawing on her own experiences as well as interviews with both moms and experts, she gets to the bottom of the toughest and most taboo topics--including how to manage nosy in-laws and an anxious partner, survive the first postpartum poop, soothe a battered nether region, and seek out treatment for depression. Enough About the Baby is filled with hacks, tips, tricks, and to-do lists that could only come from the most seasoned--and enlightened--mom"--